2021
DOI: 10.1002/lsm.23399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pulsed‐Wave Photobiomodulation Therapy on Human Spermatozoa

Abstract: Background and Objectives: Previous studies reported that photobiomodulation (PBM) positively affects the mitochondrial respiratory chain in sperm, resulting in improved motility and velocity. As laser settings are not yet fully established, the present study aimed at optimizing PBM on human sperm. In addition, possible side-effects of PBM on sperm DNA fragmentation level and acrosomal integrity have been analyzed. Study Design/Materials and Methods: A pulsed laserprobe (wavelength 655 nm, output power 25 mW/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Fragmentation greater than 30% is incompatible with the initiation and/or maintenance of pregnancy [ 27 ]. We did not identify effects of far-IR on sperm DNA fragmentation rate in agreement with studies that used other wavelengths [ 23 25 ]. Taking into account that sperm are susceptible to damage caused by ROS and other spermatogenesis processes [ 41 ], which can damage sperm DNA and consequently its viability, the far-IR irradiation by the FIR of our study shows that this therapeutic modality is safe in terms of damage to sperm DNA.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Fragmentation greater than 30% is incompatible with the initiation and/or maintenance of pregnancy [ 27 ]. We did not identify effects of far-IR on sperm DNA fragmentation rate in agreement with studies that used other wavelengths [ 23 25 ]. Taking into account that sperm are susceptible to damage caused by ROS and other spermatogenesis processes [ 41 ], which can damage sperm DNA and consequently its viability, the far-IR irradiation by the FIR of our study shows that this therapeutic modality is safe in terms of damage to sperm DNA.…”
Section: Discussionsupporting
confidence: 86%
“…It is expected that mitochondrial function and pathways modulated by ATP availability are preserved in normal semen samples, consequently sperm motility as well, since flagellum movement is highly dependent on mitochondrial energy metabolism and intracellular calcium modulation [ 25 , 38 ]. Thus, if we consider that one of the main effects observed under PBMT is the improvement of mitochondrial energy metabolism [ 39 ], the absence of effects of FIR on participant semen quality is reasonable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The radiation can improve corneal surface, alleviate inflammation through decreasing of the neutrophils levels, etc. Espey et al [ 9 ] demonstrated that PBM using 665 nm pulsed (200 ns) radiation from a DL with fluence 4 and 6 J/cm 2 results in a significant increase in sperm motility and velocity within 120 min post-irradiation.…”
Section: Introductionmentioning
confidence: 99%